The dentin thickness remaining in the risk zone of mandibular molars after cervical preflaring with four methods - Sheila Leite PINTO; Marília Fagury Videira MARCELIANO-ALVES; Renata Ximenes LINS; Ermelindo Antônio RADETIC; Hélio Pereira LOPES
Abstract Introduction Cervical preflaring is an important step of the canal system instrumentation, but can lead to excessive enlargement or root perforation. Objective Evaluate the remaining dentin thickness in the mandibular molars of mesial roots using cone beam computed tomography: Gates-Glidden (crown-down); Gates-Glidden (step-back); LA Axxess and Easy Pro-Design. Material and method Were selected 40 lower molars mesial roots, which were scanned in a cone beam CT scanner before and after preparation. Were obtained five sections of the CT images with an interval of 1 mm from the furcation, and measured the thickness variation between the root canal to the root external portion in analysis software. Result The evaluation of the different levels showed no significance within the same group for the Gates-Glidden group. On the other hand, were observed difference for LA Axxess (p=0.002) and Easy Pro-Design (p=0.005). In the intergroup analysis, were observed difference in all levels, especially for Gates-Glidden in the ascendant order (ANOVA and Tukey). Conclusion Within the limitations of these study, is possible to conclude that the protocol with greater wear in the cervical risk area was the Gates-Glidden in step-back sequence, as the other groups were equivalent (p>0.05).